POTENSI PEMANFAATAN ATAP GEDUNG UNTUK PLTS DI KANTOR DINAS PEKERJAAN UMUM, PERUMAHAN DAN ENERGI SUMBER DAYA MINERAL (PUP-ESDM) PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Defi Rizkasari; Wahyu Wilopo; Mohammad Kholid Ridwan (Journal of Appropriate Technology for Community Services, 2020)
Electricity consumption in Indonesia from year to year has increased. The sales of PLN 2018 electricity in 234,617.88 GWh covering industrial sector, household sector, commercial sector, and public sector. While electrical energy consumption in D. I. Yogyakarta in 2018 of 2,857.06 GWh covering household sector, industrial sector, business sector, social sector, government office building sector and public street lighting. In fulfilling the demand of electrical energy, Yogyakarta installed power plant consists of PLTMH, PLTBm, PLTS and PLTHybrid with an installed capacity of 4.84 MW so that electricity in Yogyakarta is supplied from the interconnection network of Java-Madura-Bali. Energy resources used by interconnection networks generally use fossil energy (coal). Therefore we need a substitute for future fossil fuels. Utilization of renewable energy is one of the solar energy optimizations that can be applied to urban areas. The building sector consumes up to 40% of total annual energy. One of the buildings that can apply the utilization of renewable energy is the office building PUP-ESDM D. I. Yogyakarta. This research aims to know the potential power generated from the PLTS roofing if it is built on the office building Public Works, housing and Energy Mineral resources (PUP-ESDM) D. I. Yogyakarta. Research is conducted by conducting energy simulations using the HelioScope software. Simulated results show the east side of Building 1, the east side of Building 2, the east side of Building 3, the west side of Building 2 and the north side of Building 2 is the optimal location of photovoltaics. The Total energy potential generated from these five roofs is 73,484.5 kWh/year and is able to supply the energy needs of the PUP-ESDM office by 74.42%.